Mediation Effect of Job Satisfaction on The Effect of Participatory Leadership Style and Individual Creativity on Senior High School Teacher Performance in Kerinci District - Herningrum, Indah; Ekawarna, Ekawarna; Khairinal, Khairinal; Hadiyanto, Hadiyanto; Sarmigi, Elex (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This research examined the effect of participatory leadership style and individual creativity on teacher performance. In addition, this research also examines whether the existence of the variable job satisfaction mediates the relationship between participatory leadership style and individual creativity on teacher performance. This research was conducted on 80 respondents who were high school teachers in Kerinci Regency. The research data was collected using an online questionnaire (google form). The data analysis technique of this research is Structural Equation Model (SEM) analysis with the help of the SmartTPLS 3.0 application. This study found that the participatory leadership style positively and significantly affects job satisfaction and teacher performance. While individual creativity does not significantly affect job satisfaction, it significantly affects teacher performance. Job satisfaction does not affect teacher performance. Job satisfaction is also not proven to be able to mediate the relationship between participatory leadership style and individual creativity on the performance of high school teachers in the Kerinci District.